Non-formal Learning Strategies in Improving the Quality of Learning - Rajaminsah; Yuni Rahmawati; Yuliana Ambarwati; Siti Nurjanah (al-Afkar, Journal For Islamic Studies, 2024)
This journal discusses Non-Formal Learning Strategies in Improving the Quality of Learning. Non-formal education is very different from formal education, as is its implementation. For this reason, different strategies are needed in the learning process of non- formal education from formal education. The background to non-formal learning strategies is the need to improve the quality of learning so that it is in line with current developments. Through the implementation of non-formal learning strategies, it is hoped that it can increase students' interest in learning, develop life skills and, ultimately, improve the overall quality of learning. This research uses a qualitative approach with a case study method. Data collection carried out in this research came from observations, interviews and documentation studies. The results of this research are the implementation of non-formal learning strategies including learning planning and design, implementation of non-formal learning involving the use of media and technology, evaluation and monitoring are also carried out periodically. challenges and obstacles in non-formal learning, such as limited resources, regulatory and policy constraints, and the role of teachers in non-formal learning.